2008
DOI: 10.1007/s11947-008-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Medium- and Long-Chain Triacylglycerols (MLCT): Optimization of Process Parameters Using Response Surface Methodology

Abstract: The main objective of this study was to understand the effects and relationship amongst four factors, which are reaction temperature, reaction time, enzyme load, and substrate mole ratio with the purpose of producing healthy functional cooking oil for long-term dietary treatment. Lipozyme RM IM lipase-catalyzed esterification of medium-and long-chain triacylglycerols (MLCT) from glycerol and mixtures of capric and oleic acid was optimized using response surface methodology (RSM) with a fivelevel, four-factoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 35 publications
3
47
1
Order By: Relevance
“…Most of the interaction terms were found nonsignificant in the response models. Koh et al (2010) reported that most of the interactions between these variables were found to be insignificant at 99% confidence level. The En*Sr interaction was only significant for the residual yield of OOO and caused a decrease in the amount of triolein.…”
Section: Effect Of Parameters and Response Surface Plottingmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of the interaction terms were found nonsignificant in the response models. Koh et al (2010) reported that most of the interactions between these variables were found to be insignificant at 99% confidence level. The En*Sr interaction was only significant for the residual yield of OOO and caused a decrease in the amount of triolein.…”
Section: Effect Of Parameters and Response Surface Plottingmentioning
confidence: 97%
“…SLs combine the unique characteristics of component fatty acids such as melting behavior, digestion, absorption, and metabolism in one triacylglycerol molecule to enhance the role fats and oils play in food, nutrition, therapeutics and health applications (Akoh and Min, 2002;Osborn and Akoh, 2002;Ciftci et al, 2009). Fatty acid composition and their position in the TAG determine the functional and physical properties, metabolic rate, and health benefits of the structured lipid (Koh et al, 2010;Çiftçi et al, 2008;Nieto et al, 1999). The main variation in the fatty acid composition of oils and fats is the chain length and degree of unsaturation of the component FA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the % of solid fat values by DSC was evaluated for the SL synthesized at optimum conditions. Table 3 shows the first five solutions predicted for the maximum synthesis of desired TAG and minimum energy under optimized conditions at which the enzyme load was set at its minimum value due to the cost consideration, while the other variables were set in the range of the studied values (Koh et al, 2010). The optimum conditions which satisfied the above requirements with high desirability (0.86) would give 58.90 (%) total produced TAG, 52.23 (%) desired TAG and 38.96 kj/g energy.…”
Section: Optimization Of Reaction Parametersmentioning
confidence: 99%
“…This result is expected as the main FA of the blends is oleic acid and OOO is the main TAG. da Silva et al (2010) reported that triunsaturated TAGs have melting points from −14 °C to 1 °C, and triolein has a melting point of −4 °C (Hynes, 2010). In the crystallization thermograms of unreacted MoO/PO blends (Figure 2), three crystallization peaks (peaks 1, 2 and 3) were observed.…”
Section: Effect Of Enzymatic Interesterifi Cation On Dsc Thermogramsmentioning
confidence: 99%
“…In addition, the MoO/VCO interesterified blends with elevated levels of MLCT may improve the quality of pastries as Ariffin et al (2010) reported that cookies made from mediumand long-chain triacylglycerol-enriched margarines have good texture and sensory perception as well as excellent nutritional benefits.…”
Section: Effect Of Enzymatic Interesterifi Cation On Solid Fat Contentmentioning
confidence: 99%